Application of Bloom's taxonomy to improve teaching-learning - Toala Ponce , Santa Rocío (2022)
Bloom's taxonomy has six levels, in cognitive processes, of complexity developed in a hierarchical manner, being inclusive and ascending. Thus helping teachers so that students can memorize the processes of the subjects, understand the information provided to them in the classroom. The purpose of this research was to see the feasibility of applying Bloom's Taxonomy to improve the online teaching of fifth-level students of the Basic Education career of the Faculty of Pedagogy of the "Luis Vargas Torres" Technical University of Esmeraldas. To carry out this work, a descriptive and qualitative research was carried out, with the use of methods such as analysis, synthesis and hermeneutics. In this case, 58 students were chosen: 38 to whom Bloom's taxonomy was applied and 20 to whom Bloom's taxonomy was not applied. Data collection was done through the grades obtained by each student. Therefore, it is concluded that the application of this strategy obtained satisfactory results in this investigation.